Effects of sucrose and glycerol on vitrification of buffalo oocytes - Hossain, M. A.; Akter, Shahrina; Miraz, M. F. H.; Islam, M. Nuronnabi; Bari, Jannatul; Alam, M. Hasanur; Sarker, M. Bodruzzaman; Kabir, M. E.; Khatun, A.; Hashem, M. A.; Moniruzzaman, M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Vitrification, ultra-rapid cooling can be used to cryopreserve oocytes for embryo technology. The objective of this study was to evaluate the effects of sucrose and glycerol on vitrification of buffalo oocytes. Methods: Cumulus-oocyte complexes (COCs) were aspirated from slaughtered buffalo ovaries. In experiment 1, the vitrification solution was supplemented with either 0, 0.25 or 0.5 M sucrose. In experiment 2, the vitrification solution was supplemented with either 0, 5 or 10 M glycerol together with 0.5 M sucrose. COCs were exposed into equilibration solution and vitrification solution for 5 min and 1 min, respectively. Then the oocytes were submerged into liquid nitrogen for 10 min using cryotops. The oocytes were thawed, diluted and washed in washing solution. Vitrified oocytes were cultured for maturation at 38.5°C for 24 hrs at 5% CO2. Then oocytes were fixed in acetic acid and ethanol and stained with aceto-orcein to examine the meiotic stages. Results: In experiment 1, a significantly higher number of morphologically normal oocytes and cumulus cell expansion were found in 0.5 M sucrose group than others. In addition, a proportion of oocytes resumed meiosis but none of those developed to the metaphase II (MII) stage. In experiment 2, a significantly higher number of oocytes showed cumulus cell expansion as well as higher morphologically normal oocytes in 5 M and 10 M glycerol than in 0 M (control) group. In addition, 18% oocytes matured to MII stage in 5 M glycerol group. Conclusions: Buffalo oocytes can be vitrified with a combination of sucrose and glycerol to maintain its developmental potential.